Application of Artificial Intelligence in Social Sciences Research in India: A Bibliometric Analysis - Awasthi, Shipra; Gupta, Brij Mohan; Vaishya, Raju; Tripathi, Manorama (Journal of Data Science, Informetrics, and Citation Studies)
This study presents a bibliometric analysis of the top 100 highly cited publications on the application of Artificial Intelligence (AI) in social sciences research in India during 2013-2024, retrieved from the Scopus database. The analysis reveals a steady annual growth rate of 13.42%, with the selected papers receiving an average of 101.2 citations per document, reflecting high scholarly impact. These publications originated from 394 authors across 73 sources, with nearly 40% resulting from international collaborations. Keyword co-occurrence and trend analyses highlight key thematic clusters, including data analytics, sentiment analysis, and social simulations, underscoring the growing interdisciplinarity between AI and social sciences. The citation structure indicates that the top 10 papers account for over half of all citations, signalling concentration of influence within a few high-impact works. The findings offer insights into India’s evolving research ecosystem, emphasizing collaborative, data-driven, and ethically grounded directions for future social science research powered by AI.
Keywords: AI; Artificial Intelligence; Bibliometrics; Collaboration Networks; India; Research Trends; Social Sciences.